Functional implications of Cav2.3 R‐type voltage‐gated calcium channels in the murine auditory system – novel vistas from brainstem‐evoked response audiometry. (3rd November 2019) - Lundt, Andreas; Soós, Julien; Seidel, Robin; Henseler, Christina; Müller, Ralf; Raj Ginde, Varun; Imran Arshaad, Muhammad; Ehninger, Dan; Hescheler, Jürgen; Sachinidis, Agapios; Broich, Karl; Wormuth, Carola; et al.
Abstract: Voltage‐gated Ca 2+ channels (VGCCs) are considered to play a key role in auditory perception and information processing within the murine inner ear and brainstem. In the past, Cav 1.3 L‐type VGCCs gathered most attention as their ablation causes congenital deafness. However, isolated patch‐clamp investigation and localization studies repetitively suggested that Cav 2.3 R‐type VGCCs are also expressed in the cochlea and further components of the ascending auditory tract, pointing to a potential functional role of Cav 2.3 in hearing physiology. Thus, we performed auditory profiling of Cav 2.3 +/+ controls, heterozygous Cav 2.3 +/− mice and Cav 2.3 null mutants (Cav 2.3 −/− ) using brainstem‐evoked response audiometry. Interestingly, click‐evoked auditory brainstem responses (ABRs) revealed increased hearing thresholds in Cav 2.3 +/− mice from both genders, whereas no alterations were observed in Cav 2.3 −/− mice. Similar observations were made for tone burst‐related ABRs in both genders. However, Cav 2.3 ablation seemed to prevent mutant mice from total hearing loss particularly in the higher frequency range (36–42 kHz). Amplitude growth function analysis revealed, i.a., significant reduction in ABR wave WI and WIII amplitude in mutant animals. In addition, alterations in WI ‐WIV interwave interval were observed in female Cav 2.3 +/− mice whereas absolute latencies remained unchanged. In summary, our results demonstrate that Cav 2.3 VGCCs are mandatory for physiological auditory information processing in the ascending auditory tract. Abstract : Cav 2.3 R‐type voltage‐gated calcium channels are expressed in the inner ear and ascending auditory tract. Heterozygous male and female Cav 2.3 +/− mice exhibit prominent increase in click‐ and tone burst‐evoked hearing thresholds as well as alterations in amplitude growth function. Cav 2.3 −/− mice display only moderate changes in the auditory profile, probably due to compensatory changes. qPCR analysis of cochleae from Cav 2.3 +/− and Cav 2.3 −/− mice reveals changes in other VGCC transcripts.